Study Of The Aerodynamic Structure Around A NACA6409 Airfoil Rotor - Gouiaa Saoussane (International Journal of Energetica)
The multi-copters are one of the important aircrafts in the world because they are used in both military and civil application. The problem of these aircrafts is the low efficiency of its propellers. That’s why, it is necessary to study the aerodynamic structure around every rotor. In this paper, a computer simulation has been done to study the aerodynamic structure around a NACA 6409 airfoil rotor. The numerical model is based on the resolution of the Navier-Stockes equations with a standard k-ε model. Then, the finite volume discretization of these equations leads to solve it. The local characteristics of the aerodynamic structure are extracted using the software Solidworks Flow Simulation and the validation is done with comparison with anterior result of Alexandrov (2013).